2012
DOI: 10.1074/jbc.m112.378331
|View full text |Cite
|
Sign up to set email alerts
|

Starch Source Influences Dietary Glucose Generation at the Mucosal α-Glucosidase Level

Abstract: Background: ␣-Amylase was thought to be the sole enzyme that determines starch digestion rate. Mucosal ␣-glucosidases were considered to simply convert post-␣-amylase dextrins to glucose. Results: The mucosal ␣-glucosidases can digest a wide range of ␣-limit dextrin molecules and digest starches from various sources differently. Conclusion: Starch chemical structure drives the digestion difference at the brush-border area. Significance: The findings provide new insight into controlling the glycemic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…Previous investigations showed 10-20 times higher amount of SI than MGAM protein in the proximal part of the small intestine [3,45]. In the present study, the protein amount of ctMGAM was 5-15 times lower compared to the other three ␣-glucosidases [13]. Thus, the ratio of amount of the most active ctMGAM is similar to that found in the upper level of the small intestine.…”
Section: Ctmgam Is Required For Full Hydrolysis Of Partially Hydrolyzsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous investigations showed 10-20 times higher amount of SI than MGAM protein in the proximal part of the small intestine [3,45]. In the present study, the protein amount of ctMGAM was 5-15 times lower compared to the other three ␣-glucosidases [13]. Thus, the ratio of amount of the most active ctMGAM is similar to that found in the upper level of the small intestine.…”
Section: Ctmgam Is Required For Full Hydrolysis Of Partially Hydrolyzsupporting
confidence: 83%
“…These enzymes have different hydrolysis properties on different chain-length oligosaccharides [14,15] and ␣-glucosidic linkages [11]. Our group has found uniquely high hydrolysis property of the ctMGAM particularly for native dispersed starch molecules [6,13].…”
mentioning
confidence: 99%
“…The glucogenesis by the intestinal extract hydrolysis was a combination of direct hydrolysis of starch and the conversion of malto-oligosaccharides to glucose. These two types of hydrolytic reactions on various starches were different due to the difference of starch internal structures [29]. Taken together, this study showed that mucosal α-glucosidases are able to individually break down granular starch to some degree, and can alter the way in which α-amylase hydrolyzes granular starch and dextrins.…”
Section: Discussionmentioning
confidence: 82%
“…A recent report demonstrates that brush border enzymes also hydrolyze large starch molecules in vitro (Lin et al, 2012). The timeline of digestion and the release of energy for the body in the form of glucose are major physiological properties of starch.…”
Section: Physiological Effects Of Rapidly Digestible Slowly Digestibmentioning
confidence: 99%